Dialogical and Integrated Self in Late Adulthood: Examining Two Adaptive Ways of Growing Old - Filip, Miroslav; Lukavská, Kateřina; Šolcová, Iva Poláčková (International journal of aging & human development, 2020)
We examined two contradictory views of Erikson's concept of ego integrity: as an outcome of the tension between integrity and despair, or as a dialogical process of balancing positive and negative life experiences. One hundred sixty-seven Czech older adults participated in the study. Dialogically integrated, outcome-integrated, and outcome-despairing participants were selected based on the Ego Integrity Scale and based on methods mapping life-reviewing dialogue. The three subsamples were compared in their psychological adaptation. The results showed that the dialogically integrated participants scored similarly in well-being and meaningfulness of life as outcome-integrated participants and better than outcome-despairing participants. However, the dialogically integrated participants were also prone to experiencing negative emotions. As they were older than the other two subsamples and reported worse physical health, we concluded that the life-reviewing dialogue helps them maintain a sense of meaning in life and a certain level of well-being. Hence, the results support relevance of the dialogical-process view.
Keywords: sebepojetí; Aged; Adaptation, Psychological; dospělí; ego; Adult; Life Change Events; Ego; Humans; senioři; lidé; životní změny; Self Concept; adaptace psychologická